How do local gender norms interact with local conceptualisations of empowerment to shape women's engagement in local dairy value chains in Tanzania? - Achandi, Esther L.; Farnworth, Cathy Rozel; Galiè, Alessandra; Omore, Amos O.; Jeremiah, Adolf (Frontiers Media, 2023)
Women play important roles in the dairy sector in Tanzania yet many women face local gender norms which inhibit them from benefitting from their enterprises. This affects women's empowerment and the development of effective livestock businesses.This study addresses the question: How do women's empowerment and gender norms affect women's engagement in livestock business? To respond, this study explores how women attempt to negotiate gender norms in order to create a niche for their agribusiness, and thereby to empower themselves. Since gender norms are diverse, research was undertaken in 2021 with agripreneurs running dairy-related businesses in two regions of Tanzania. Gender-disaggregated focus group discussions, key informant interviews, and individual interviews were carried out in Kilimanjaro and Tanga regions which had been target sites for the bigger Maziwa Zaidi Phase II project in Tanzania. In total, 24 women dairy farmers, 25 men dairy farmers, 20 women agripreneurs and 22 men agripreneurs involved in selling feeds, milk collection and agro-veterinary goods and services such as artificial insemination and livestock extension participated in the FGDs. Twelve women and 16 men were interviewed as KIIs while 12 women and 15 men were interviewed individually.Moreover through gender norms gatekeeping, significant relations such as husbands and community members can also act as empowerment gatekeepers reining in women's expression and experience of empowerment, especially if her husband is economically disempowered while she is.